FORMULASI SEDIAAN GEL HAND SANITIZER EKSTRAK BIJI PINANG (ARECA CATECHU L.) SEBAGAI ANTIBAKTERI - Rahayu Mustika, Sari (Journal of Pharmacy Tiara Bunda, 2022)
The usage of hand antiseptic gel in gel form has become a lifestyle on middle to upper class citizen. Various antiseptic products; especially antiseptic gel hand sanitizer has been wildly developed. Antiseptic was made in gel form because of it is convenience and spread evenly upon contact to skin and nice to used because it feels cold on skin caused gel contains a lot of water. This product were considered effective in killing bacteria on hands, as a method to reduce the amount of bacteria that enter the body. Areca nut has a metabolite compound such as tanin and flavonoid that hasantibacterial effect. To know the antibacterial activity of Areca nut extract (Areca catechu L.) along with formulating hand sanitizer gel from Areca nut extract and to know the antibacterial activity ofgel hand sanitizer from Areca nut extract.Making of Areca nut extract by soxhlet using ethanol 96% solvent and evaporated in waterbath to one third. The extract of Areca nut conducted antibacterialactivity test with concentration of 500 mg/mL, 400 mg/mL, 300 mg/mL, 200 mg/mL, 100 mg/mL, 50 mg/ml, 40 mg/mL, 30 mg/mL, 20 mg/mL, 10mg/mL, 5 mg/mL. The extract of Areca nut were made into hand sanitizer gel withconcentration of (F1) 300 mg/mL, (F2) 350 mg/mL, and (F3) 400 mg/mL.Evaluation of gel preparations included organoleptic, pH, homogeneity and dispersibility.The preparation of areca nut (Areca catechu L.) hand sanitizer gel with concentrations of 30%, 35%, and 40% had good physical properties